1983
DOI: 10.1021/ci00040a009
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted examination of compounds for common three-dimensional substructures

Abstract: A program for finding common three-dimensional substructures within a set of chemical compounds is described. The program allows a user to define what constitutes commonality of substructures by providing control over the importance of degree of substitution, atom type, aromaticity, and hybridization. Simple examples are used to illustrate various phases of the search process, and an application of the program to a structure/activity problem is used as a more realistic example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…In some cases, this is because they are by now very old, such as the seminal -and I use the word advisedly -contributions by Ray and Kirsch [32] and by Vleduts [33] to the searching of molecules and of reactions, respectively. In other cases, the original work was over-shadowed by subsequent publications: for example, the 1981 paper by Lynch et al [34] was merely the first in a sequence of over twenty publications on the representation and searching of generic structures; and the 1983 graph-matching paper by Crandell and Smith [35] resulted a decade later in the first successful commercial system for pharmacophore mapping [36] (vide infra). In still other cases, the importance of the work was simply not fully recognised at the time, e.g., the paper by Adamson and Bush [37] on comparing fragment bit-strings to compute molecular similarity preceded the first descriptions of similarity searching systems by over a decade [38,39]; indeed, it was this 1973 paper that was one of the principal drivers for work in Sheffield on fingerprint-based searching and clustering that commenced in the Eighties [40] and that continues to the present day [41].…”
Section: Selection Of Key Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, this is because they are by now very old, such as the seminal -and I use the word advisedly -contributions by Ray and Kirsch [32] and by Vleduts [33] to the searching of molecules and of reactions, respectively. In other cases, the original work was over-shadowed by subsequent publications: for example, the 1981 paper by Lynch et al [34] was merely the first in a sequence of over twenty publications on the representation and searching of generic structures; and the 1983 graph-matching paper by Crandell and Smith [35] resulted a decade later in the first successful commercial system for pharmacophore mapping [36] (vide infra). In still other cases, the importance of the work was simply not fully recognised at the time, e.g., the paper by Adamson and Bush [37] on comparing fragment bit-strings to compute molecular similarity preceded the first descriptions of similarity searching systems by over a decade [38,39]; indeed, it was this 1973 paper that was one of the principal drivers for work in Sheffield on fingerprint-based searching and clustering that commenced in the Eighties [40] and that continues to the present day [41].…”
Section: Selection Of Key Papersmentioning
confidence: 99%
“…This limitation was first overcome in a study by Crandell and Smith [35], who described the use of an MCS algorithm to find 3D patterns common to sets of molecules. The work was carried out as an aid to structure elucidation (see below) but is also clearly applicable to the problem of pharmacophore mapping.…”
Section: Quantitative Structure-activity Relationships and Molecular mentioning
confidence: 99%
“…Examples for such methods include the CrandellSmith method [13], RAPID [14] and HipHop [15][16][17]. In other methods information about inactive ligands is also used.…”
Section: Inputmentioning
confidence: 99%
“…The Barakat-Dean algorithm is an example of an algorithm that was originally proposed in a 3D formulation, and so is the algorithm described by Crandell and Smith [78], although even this owes much to the algorithm of Varkony et al [66], in that it attempts to "grow" a 3D MCIS iteratively. The Crandell-Smith algorithm was studied in detail by Brint and Willett [42], who found that a clique-based method using the Bron-Kerbosch algorithm was generally to be preferred for the identification of the 3D…”
Section: D-specific Algorithmsmentioning
confidence: 99%